2021
DOI: 10.1021/acsami.1c11256
|View full text |Cite
|
Sign up to set email alerts
|

Atomically Resolved Characterization of Optically Driven Ligand Reconfiguration on Nanoparticle Catalyst Surfaces

Abstract: Dynamic ligand layers on nanoparticle surfaces could prove to be critically important to enhance the functionality of individual materials. Such capabilities could complement the properties of the inorganic component to provide multifunctionality or the ability to be remotely actuated. Peptidebased ligands have demonstrated the ability to be remotely responsive to structural changes when adsorbed to nanoparticle surfaces via incorporation of photoswitches into their molecular structure. In this contribution, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Once the photoswitch/peptide bioconjugate was adsorbed to the NP surface, reversible changes in the biomolecular overlayer can subsequently be achieved via photoswitching of the azobenzene moiety. These changes have been confirmed computationally and spectroscopically, , which can be exploited to modulate the catalytic properties of the materials. For instance, varied reactivity for the reduction of 4-nitrophenol to 4-aminophenol was observed for peptide-capped Au NPs with the photoswitch in either the cis or trans configurations. , In this case, the effect was noted to be controlled via changes in the activation energy or the pre-exponential factor of the reaction as dictated by the specific NP/peptide combination. ,, Subsequent research has demonstrated further understanding of this photoswitch effect on catalysis as a function of peptide sequence, photoswitch position, bioligand heterogeneity, and NP inorganic composition; ,,, however, such effects have only been observed for one single reaction: 4-nitrophenol reduction.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Once the photoswitch/peptide bioconjugate was adsorbed to the NP surface, reversible changes in the biomolecular overlayer can subsequently be achieved via photoswitching of the azobenzene moiety. These changes have been confirmed computationally and spectroscopically, , which can be exploited to modulate the catalytic properties of the materials. For instance, varied reactivity for the reduction of 4-nitrophenol to 4-aminophenol was observed for peptide-capped Au NPs with the photoswitch in either the cis or trans configurations. , In this case, the effect was noted to be controlled via changes in the activation energy or the pre-exponential factor of the reaction as dictated by the specific NP/peptide combination. ,, Subsequent research has demonstrated further understanding of this photoswitch effect on catalysis as a function of peptide sequence, photoswitch position, bioligand heterogeneity, and NP inorganic composition; ,,, however, such effects have only been observed for one single reaction: 4-nitrophenol reduction.…”
Section: Introductionmentioning
confidence: 74%
“…These changes have been confirmed computationally and spectroscopically, , which can be exploited to modulate the catalytic properties of the materials. For instance, varied reactivity for the reduction of 4-nitrophenol to 4-aminophenol was observed for peptide-capped Au NPs with the photoswitch in either the cis or trans configurations. , In this case, the effect was noted to be controlled via changes in the activation energy or the pre-exponential factor of the reaction as dictated by the specific NP/peptide combination. ,, Subsequent research has demonstrated further understanding of this photoswitch effect on catalysis as a function of peptide sequence, photoswitch position, bioligand heterogeneity, and NP inorganic composition; ,,, however, such effects have only been observed for one single reaction: 4-nitrophenol reduction. No significant understanding of the specific catalytic reaction on photoswitchable catalysis has been considered, which is highly important to understanding such effects on controlling the catalytic properties of inorganic NPs.…”
Section: Introductionmentioning
confidence: 74%
“…For the reduction of 4-NP, standard reaction procedures were employed. Briefly, 1.8 mL of 0.05 mM peptide-capped Au nanoparticles in buffer was mixed with 80 μL of 0.320 mM 4-NP, which was stirred for 5 min. To this mixture, 120 μL of 2.0 M aqueous NaBH 4 was added.…”
Section: Methodsmentioning
confidence: 99%
“…Stimuli-responsive polypeptides have found use in drug-delivery and biomedicine including biomaterials for wound healing, and cancer treatment among many others. Stimuli-responsive peptides have also been utilized to modulate the reactivity of catalytic surfaces. By incorporating a non-natural amino acid containing azobenzene, the configuration of a peptide can be switched because azobenzene assumes a cis configuration when exposed to UV light, and a trans configuration when exposed to white light. Surface-bound peptides containing an azobenzene moiety have been demonstrated to modulate the amount of catalytic surface covered by the peptides, and thus modulate reactivity.…”
Section: Designing Peptides and Polypeptidesmentioning
confidence: 99%